Herb Stovel and authenticity in World Heritage conservation practice - Cameron, Cristina (Conversaciones con..., 2020)
The 2008 article in the APT Bulletin by Herb Stovel focuses on the impact of the authenticity debate on the conservation of built heritage, particularly on World Heritage sites. Stovel describes discussions leading up to the important international meeting in 1994 in Nara, Japan and assesses the impact of the Nara document on authenticity on conservation practice. This paper examines Stovel’s article from four perspectives: the origins of the authenticity debate, theoretical advances made at Nara, conservation practice, and the incomplete theorization of integrity. It supplements Stovel’s paper by deepening the pre-Nara context and by furthering consideration of the impacts of the Nara document on conservation practice. It explores unfinished business with regard to the application of integrity to cultural World Heritage sites. The paper also adds passages from Stovel’s insightful 2011 interviews for the World Heritage Oral Archives program, thereby offering a glimpse of the evolution of his thinking on these issues after 2008.